Full-duplex massive MIMO with physical layer network coding for the two-way relay channel - Lemos, J. S. (2016)
The role of interference in wireless networks has recently been profoundly re-thought with the emergence of new techniques for combating it and exploit it to maximize the use efficiency of the physical resources. This paper presents a two-way relay channel using a lattice-based physical layer network coding scheme, a massive MIMO array, and in-band full-duplex, taking into account the residual self-interference that results after applying recently developed cancellation techniques for the loopback interference. The proposed scheme is able to ultimately exchange information across the TWRC in only one time slot, whereas four time slots would be needed in a conventional TWRC. The system's performance is shown to be mostly dependent on the number of antennas at the relay, and also dependent on the channel state information of all the channel matrices, including the one describing the loopback interference at the relay. For base-stations and relays with a few hundred antennas, the proposed scheme is feasible for wireless systems.